PERILAKU HIDUP BERSIH DAN SEHAT SISWA KELAS VII (TUJUH) SMP NEGERI 11 BINTAN KEPRI SELAMA MASA PANDEMI COVID-19 - Muhammad Hardiyansyah; Ramadi Ramadi; Rusmanto Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research was due to the Corona virus (Covid-19) outbreak in Indonesia in early 2020. The government tried to prevent the spread of the Corona virus outbreak through a PHBS (Clean and Healthy) program. Living Behaviour). . The PHBS program in schools is expected to adopt a healthy lifestyle to create a healthy school and environment around the school. The aim of this research was to determine the clean and healthy behavior students of SMP Negeri 11 Bintan Kepri during the Covid-19 Pandemic Period. The population in this research were students of Class VII SMP Negeri 11 Bintan Kepri using a random sampling technique of a total of 120 students. The instrument used in this research is the use of a questionnaire completed by students. Based on the results and discussions described in the previous section, it can be concluded that a clean and healthy lifestyle has a good impact or influence on students during the COVID-19 pandemic. Based on the results of the calculation of the ideal score, a score of 3452 points out of 4500 or 76.71% was achieved in the good category.Key Words: Clean and Healthy Living Behavior at School